Perceived Behavioural Control and Subjective Norms Influence on Entrepreneurial Intention - Nizar Alam Hamdani; Muhammad Fathulloh Ramdani; Dinda Sri Puspita; Intan permana (Cita Konsultindo Research Center, 2024)
Entrepreneurial intention is an individual's desire or motivation to become an entrepreneur and start a business. Gen Z generation in Indonesia has a business interest below average at 1.60%, compared to the country's average of 18.94%. Increasing entrepreneurial interest in the Gen Z generation requires an approach and creating an environment that develops entrepreneurial potential. This researcher conducted a survey online and face-to-face to collect data from 115 randomly selected participants. The response rate was 50.4%, and 73 participants completed the survey, representing approximately 30.43% of the total sample. Therefore, the sample size for this study was 58 respondents who provided varying assessments. Researchers also distributed respondents only to the Gen Z age group for all items. Researchers provided questionnaires with surveys directly and sent them online. The tool researchers used to get respondents was questionnaires. The program used to analyze data using the regression method is Statistical Product and Service Solution (SPSS). To perform regression analysis on an interval scale, researchers use arithmetic calculations on data collected from respondents. The research results are accurate and reliable, with a significance level of 95%. Results of research regarding perceived behavioral control and subjective norms influence entrepreneurial intention. Based on the results of this research, the researchers expected that these results would be helpful to respondents and readers so that they could be used in further study.